2015
DOI: 10.1039/c4nj02261k
|View full text |Cite
|
Sign up to set email alerts
|

The S-hindered synthesis of PbSe/PbS nanosheets with enhanced electrochemical activities

Abstract: A one-step synthesis of PbSe/PbS nanosheets for a Li ion battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It is well-known, that creation of hybrids and nanocomposites, having properties that are not typical for microscale materials, is a promising way to design an advanced electrodes for LIBs. Additionally, as it was shown previously, the usage of Sn or Pb in a form of oxides [6,7], chlorides [8,9], fluorides [10], sulfides [11,12], etc. facilitate the volume stresses due to the formation of damping matrices during initial alloying process (1).…”
Section: Introductionmentioning
confidence: 61%
“…It is well-known, that creation of hybrids and nanocomposites, having properties that are not typical for microscale materials, is a promising way to design an advanced electrodes for LIBs. Additionally, as it was shown previously, the usage of Sn or Pb in a form of oxides [6,7], chlorides [8,9], fluorides [10], sulfides [11,12], etc. facilitate the volume stresses due to the formation of damping matrices during initial alloying process (1).…”
Section: Introductionmentioning
confidence: 61%
“…PbSe NSs were utilized for harmonic mode locking in fiber lasers [43]. Li-ion battery performances were also enhanced using PbSe/PbS NSs [48].…”
Section: Applicationsmentioning
confidence: 99%
“…In literature, only few research groups' report the synthesis of PbSe NSs, however, the thickness of the reported NSs is not enough to show the quantum confinement effect. 83,84 Here, we have developed a novel synthesis method for synthesizing the quantum confined PbSe NSs of sufficient thickness. The setup, as shown in Figure 2.4 was enacted by carving out a parallel cavity in a domestic microwave oven that allowed a quartz enclosure with an outer diameter of 19 mm to pass through it.…”
Section: Pbse Nanosheets (Nss)mentioning
confidence: 99%